New concepts of radiologic preoperative evaluation of anterior shoulder instability: on-track and off-track lesions. (August 2018) - Gulati, Aishwarya; Dessouky, Riham; Wadhwa, Vibhor; Sanders, Drew; Chhabra, Avneesh
The shoulder is the most frequently dislocated joint in the body due to a larger range of motion and a small area of articulation between the humeral and glenoid surfaces. Traumatic shoulder dislocations, especially those associated with injury to the labroligamentous or bony stabilizers of the joint, lead to further reduction of articular surface contact with resultant glenohumeral instability and recurrent shoulder dislocations. Imaging plays an increasingly important role in the preoperative evaluation of patients with traumatic shoulder instability by evaluating glenohumeral bone loss (uni- or bipolar), assessing soft tissue injuries and identifying patients at risk of postoperative recurrence. Quantification of bone loss is key to differentiate engaging vs. non-engaging Hill–Sachs lesions, while newer concepts of "on-track" vs. "off-track" lesions are being discussed that can determine the required surgical approaches. In this article, we review the preoperative imaging approaches, traditional treatments, outline the bone loss measurement strategies and review these new tracking concepts with relevant case examples.